Intercultural comparison of patient satisfaction with physiotherapy care in Australia and Korea: an exploratory factor analysis. (1st May 2013) - Hush, Julia M; Lee, Haejung; Yung, Vivian; Adams, Roger; Mackey, Martin; Wand, Benedict M; Nelson, Roger; Beattie, Paul
Abstract : Objectives: The aim of this study was to conduct a cross-cultural comparison of the factors that influence patient satisfaction with musculoskeletal physiotherapy care in Australia and Korea. Methods: Prospective studies were conducted in Australia and Korea. Patient satisfaction data were collected using the MedRisk Instrument for Measuring Patient Satisfaction with Physical Therapy Care (MRPS) from a total of 1666 patients who were attending clinics for physiotherapy treatment of a musculoskeletal condition. Exploratory factor analysis was conducted to identify factors determining patient satisfaction in each cohort. Results: A four-factor solution for the MRPS was found for the Australian and Korean data sets, explaining 61 and 55% of the variance respectively. Communication and respect, convenience and quality time and person-focused care were factors common to both countries. One factor unique to Korea was courtesy and propriety. For both cultures, global patient satisfaction was significantly but weakly correlated with the outcome of treatment. Conclusions: The interpersonal aspect of care, namely effective communication and respect from the therapist, appears to be the predominant and universal factor that influences patient satisfaction with physiotherapy care, although other culturally specific factors were identified. Physiotherapists can maximize patient satisfaction with care by addressing those features that uniquely contribute to patient satisfaction in the cultural context in which they are working.